Cleptoparasitismo intra e interespecífico en una colonia mixta de gaviotines Real (Sterna maxima) y Pico Amarillo (S. eurygnatha) - Quintana, Flavio Roberto (1997)
Within seabirds, terns are frequently affected by foodrobbing. We document the occurrence of kleptoparasitism at a mixed-species colony ofRoyal (Sterna maxima) and Cayenne (S. eurygnatha) terns at Punta León, Chubut. In two seasons we observed both inter- and intra-specific food robbing by adult terns. The amount of food lost to pirates was relatively low, only 2% of prey brought back by the terns (n = 1127). Intra-specific food robbing was higher than inter-specific kleptopatasitism in the Royal Tern and similar in the Cayenne Tern. The percentage of food lost topirates in thecolony(2.1%,n = 921)wassimilarthan in groupsoftem chicksat the beach(2.4%, n = 206). Kleptoparasitismbetweentems at PuntaLeón appears to be of 1ittle importance with respect to its effectsonbothtem populations.